Health information in a changing world practical approaches for teachers, schools, and school librarians - Lukenbill, W. Bernard; Immroth, Barbara Froling (Libraries Unlimited, 2010)
Schools, libraries, and health education -- Health curriculum and instruction -- Teaching and holistic health information literacy -- Searching for health information and developing library use skills -- Materials for health instruction and information -- Literature, the arts, performance activities, and languages -- Connections to good health : social and behavioral sciences, and languages -- Connections : health, physical education, science, and mathematics -- Globalization, instruction, and youth health -- Outreach, health, and the school community -- Into the future : health, curriculum, and librarians